A critical review on approaches to regulate the release rate of bioactive compounds from biopolymeric matrices. (15th July 2022) - Sabaghi, Moslem; Tavasoli, Sedighe; Hoseyni, Seyedeh Zahra; Mozafari, M.R.; Degraeve, Pascal; Katouzian, Iman
Graphical abstract: Highlights: Delivery of bioactives is feasible by designing biopolymer-based matrices. Nanoencapsulation protects bioactive ingredients against undesirable conditions. Mixing polymers is a practical strategy to regulate release rate. Cross-linkers reinforce the structure of biopolymeric networks. Cross-linking between polymer chains improves the release rate. Abstract: Recently, there has been a growing interest in novel food formulations and packaging materials using controlled release systems in order to enhance the functional performance of food bioactive ingredients and to prolong the shelf-life of food products. Correspondingly, numerous types of matrices (polymers, biopolymers, synthetic materials) could be implemented as carriers based on their compatibility with the bioactive ingredients and the type of releasing medium. A plethora of applications of controlled release can be identified in the pharmaceutical, agriculture, cosmetics, and particularly the food industries. Moreover, several physical and chemical stimuli are applied to regulate the release behavior of a bioactive molecule in the desired medium, which is under development. This review highlights the strategies applied to regulate the release rate of biopolymeric networks mainly including mixing of biopolymers, physical and chemical crosslinkers along with encapsulation systems, furthermore, the future prospects of release concept are discussed.